A Child Language Acquisition in Indonesian and English Language: A Longitudinal case study - somariah fitriani (UIN Salatiga, 2019)
Learning a dual language at the same time during early childhood has caused the wrong perception. Its false perception makes the parents delay the start of learning a second /foreign language. Therefore, This study aims at analyzing the first and second language acquisition of a child in the Indonesian Language and English. The issues concentrated on the spoken utterances in Indonesian and English and its affecting factors. The research adopted a qualitative approach by using a case study, as the unit analysis is a child of 3 years old. For data collection, I employed The naturalistic approach, which I kept daily notes on the progress of a child’s linguistic and recorded the dialogues. Since it is a longitudinal study, the research was conducted for two years, from 2014 to 2015. The research has revealed that utterances spoken have primarily increased and the child has already understood the commands by following the instructions. Some concepts such as feeling, taste, color, and numbers as well as short phrases and simple words in Indonesian and English at the same time can be understood and uttered. She also can change the affirmative sentence to question in term of objects she sees in her surrounding. Factors such as linguistic inputs, imitation, environment, and significant others as exposure, and language acquisition device affect a child utterance. Thus, it indicates that two languages can be taught at the same time at an early age, and it doesn’t cause misunderstanding or confusion utterance, language acquisition, exposure, L1 and L2